Models sorption of cyhalofop-butyl, on mesopotamic agricultural soils - Michellod, Alcides Martín Miguel (2020)
The adsorption equilibrium of butyl (2R)-2-[4-(4-cyano-2-fluorophenoxy) phenoxy]propanoate (CB) was studied in rice-growing soil. The equilibrium sorption data were fitted into Langmuir, Temkin and Dubinin– Radushkevich (DRK) isotherms. Of the four adsorption isotherm, the R2 value of Dubinin–Radushkevich isotherm model was the highest. The maximum monolayer coverage (qm) from Langmuir isotherm model was determined to be 0.079 mg g-1 , the separation factor indicating a favorable sorption experiment is 0.38. The heat of sorption process was estimated from Temkin Isotherm model to be 0.0004 J mol-1 and the mean free energy was estimated from DRK isotherm model to be 7.0 KJ mol-1 which vividly proved that the adsorption experiment followed a physical process.